Proceedings of the 4th International Conference on Management, Economics and Business (ICMEB 2019) 2020
DOI: 10.2991/aebmr.k.200205.049
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Best Model of Purchase Decision Through Online Store in Indonesia from the Lens of Price Perception, Service Quality and Marketing Communication

Abstract: This study aims to discuss the effect of purchasing decisions online in the marketplace. The object of research is a seller who has a good reputation and significant transactions in selling in Bukalapak e-commerce. The independent variables obtained from the preliminary survey results to the buyer are the perception of price, service quality, and marketing communication. This study uses SEM data analysis techniques and data processing using PLS. The population is e-commerce Bukalapak customers who shop at Farq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Quality of Service can be measured through various dimensions, including reliability (reliability), responsiveness (responsiveness), guarantee (assurance), empathy (Empathy), and certainty (Tangible). Each of these dimensions covers various aspects of a customer's interaction with a service provider [6]. Studies have shown that service quality can significantly influence usage behavior and customer behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of Service can be measured through various dimensions, including reliability (reliability), responsiveness (responsiveness), guarantee (assurance), empathy (Empathy), and certainty (Tangible). Each of these dimensions covers various aspects of a customer's interaction with a service provider [6]. Studies have shown that service quality can significantly influence usage behavior and customer behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Good Quality of Service can also trigger a positive WOM. Satisfied customers tend to give positive recommendations to others, which can help expand the user base or potential customers [6].…”
Section: Introductionmentioning
confidence: 99%